Transcranial Current Stimulation Alters the Expression of Immune-Mediating Genes - Rabenstein, Monika; Unverricht-Yeboah, Marcus; Keuters, Meike Hedwig; Pikhovych, Anton; Hucklenbroich, Joerg; Vay, Sabine Ulrike; Blaschke, Stefan; Ladwig, Anne; Walter, Helene Luise; Beiderbeck, Magdalena; Fink, Gereon Rudolf; Schroeter, Michael; et al. (Frontiers in Cellular Neuroscience, 2019)
Despite its extensive use in clinical studies, the molecular mechanisms underlying the effects of transcranial direct current stimulation (tDCS) remain to be elucidated. We previously described subacute effects of tDCS on immune- and stem cells in the rat brain. To investigate the more immediate effects of tDCS regulating those cellular responses, we treated rats with a single session of either anodal or cathodal tDCS, and analyzed the gene expression by microarray; sham-stimulated rats served as control. Anodal tDCS increased expression of several genes coding for the major histocompatibility complex I (MHC I), while cathodal tDCS increased the expression of the immunoregulatory protein osteopontin (OPN). We confirmed the effects of gene upregulation by immunohistochemistry at the protein level. Thus, our data show a novel mechanism for the actions of tDCS on immune- and inflammatory processes, providing a target for future therapeutic studies.